Stages of Diversification in a Neoclassical World - Catia Batista; Jacques Potin (Institute for the Study of Labor (IZA), 2013)
Recent research has documented a U-shaped industrial concentration curve over an economy's development path. How far can neoclassical trade theory take us in explaining this pattern? We estimate the production side of the Heckscher-Ohlin model using industry data on 44 developed and developing countries for the period 1976-2000. Decomposing the implied changes in industrial concentration over time shows that at least one third of these changes seems to be explained by a Rybczynski effect. This result suggests that capital accumulation led poor countries to diversify their industrial production, while rich countries made their production more concentrated in highly capital-intensive industries.
Keywords: F11; L16; O40; 330; economic growth and international trade; Heckscher-Ohlin; diversification; specialization; industrial concentration; structural change